Proceedings of the 11th International Modal Analysis Conference, February 1-4, 1993, Hyatt Orlando Hotel and Convention Center, Kissimmee, Florida - International Modal Analysis Conference (11th : 1993 : Kissimmee, Florida); Union College. Graduate and Continuing Studies; Society for Experimental Mechanics (Schenectady, NY : Union College, 1993)
09